Investigation of Distributed Search Engine Based on Hadoop - Ning Chen; Chai Xiangyang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
his paper begins with a review on the research status of search engine, followed by discussion on goals of search engine, and then the principle of distributed computing is explained. Consequently the MapReduce distributed computing model and the Hadoop distributed file system (HDFS) are analyzed in detail. Finally the distributed search engine architecture is presented. On the basis of the architecture, future challenges and opportunities of the distributed search engine are highlighted.